2017
DOI: 10.1088/1367-2630/aa5a70
|View full text |Cite
|
Sign up to set email alerts
|

Inverse counting statistics based on generalized factorial cumulants

Abstract: We propose a procedure to reconstruct characteristic features of an unknown stochastic system from the long-time full counting statistics of some of the system's transitions that are monitored by a detector. The full counting statistics is conveniently parametrized by so-called generalized factorial cumulants. Taking only a few of them as input information is sufficient to reconstruct important features such as the lower bound of the system dimension and the full spectrum of relaxation rates. The use of genera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 70 publications
0
16
0
Order By: Relevance
“…As we will see in the following, the factorial moments and cumulants provide a convenient description of the single-electron micromaser. In particular, while ordinary cumulants are useful to describe continuous random variables, factorial cumulants are in some cases better suited to characterize discrete random variables, such as the number of counted electrons or photons [56][57][58][59][60][61][62][63][64][65][66][67].…”
Section: Full Counting Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…As we will see in the following, the factorial moments and cumulants provide a convenient description of the single-electron micromaser. In particular, while ordinary cumulants are useful to describe continuous random variables, factorial cumulants are in some cases better suited to characterize discrete random variables, such as the number of counted electrons or photons [56][57][58][59][60][61][62][63][64][65][66][67].…”
Section: Full Counting Statisticsmentioning
confidence: 99%
“…Here, by contrast, we show how the phase transitions can be directly observed from accurate measurements of the full counting statistics. In particular, we will see that factorial moments and factorial cumulants [56][57][58][59][60][61][62][63][64][65][66][67] are particularly useful to reveal the non-equilibrium phase transition, which may be observed in future experiments.…”
Section: Introductionmentioning
confidence: 99%
“…so we see that the long-time limit necessarily restricts cumulants to the zero-frequency power regime, where they potentially miss important short-time physics. Counting statistics at finite times, or rather finite frequencies, remain an active theoretical [87][88][89][90][91][92][93][94] and experimental [67] research area; non-Poissonian behavior of higherorder cumulants, for example, has been shown to depend on frequency [95]. Time-dependent current cumulants are able to identify short-time correlations between electrons [96,97]; in fact it has been proposed that higherorder factorial cumulants can be used as a detection technique for electron-electron interactions [98][99][100].…”
Section: Fixed-time Statisticsmentioning
confidence: 99%
“…3(a) with a solid line, which shows its decaying character. Even though there is an underlying but complex relation between the exponent spectrum and the cumulants [40], the moments µ m = ∞ 0 t m P e (t)dt and the associated cumulants κ m [41] depicted in Fig. 3(b) do not provide direct information about the topology.…”
Section: Introductionmentioning
confidence: 99%